2023
DOI: 10.1021/acsanm.3c01088
|View full text |Cite
|
Sign up to set email alerts
|

Smart-Phone-Assisted Optical Biosensors Based on Silk-Fibroin-Decorated Reduced Graphene Oxide Quantum Dots for Fluorescent Turn-On Recognition of l-Dopa

Abstract: Levodopa (l-dopa) is a gold standard neurological drug for symptomatic medication of Parkinson’s disease. The long-term use of l-dopa therapy frequently leads to l-dopa-induced dyskinesia and several other non-motor flocculants for fluctuating plasma concentration. To alleviate the adverse effect of dopamine replacement therapy, sensitive detection of l-dopa is still challenging. Therefore, this study presents a simple strategy to develop an inexpensive, easy-to-use, smartphone-based fluorescence turn-on senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 71 publications
(126 reference statements)
0
7
0
Order By: Relevance
“…27 Furthermore, a paper-based sensing matrix integrated with smartphone-based measurement facilitates point-of-care analysis biosensors not only for monitoring and diagnosing cancer but also for other diseases. 28 In this work, PNP-modified paper was used to immobilize antibodies, followed by PSA and detection probe binding. Different concentrations (5, 10, 25, 50, 100, and 120 ng ml −1 ) of PSA standard were used to bind to the sensor surface.…”
Section: Resultsmentioning
confidence: 99%
“…27 Furthermore, a paper-based sensing matrix integrated with smartphone-based measurement facilitates point-of-care analysis biosensors not only for monitoring and diagnosing cancer but also for other diseases. 28 In this work, PNP-modified paper was used to immobilize antibodies, followed by PSA and detection probe binding. Different concentrations (5, 10, 25, 50, 100, and 120 ng ml −1 ) of PSA standard were used to bind to the sensor surface.…”
Section: Resultsmentioning
confidence: 99%
“…Analyzing the red, green, and blue values through a mobile app revealed a matching LOD of 0.29 M within a similar concentration range. This economical and swift screening technique, suitable for remote areas lacking sophisticated instrumentation, holds promise for on-the-spot analyte detection [ 99 ].…”
Section: Nanotechnology Mediated Biosensorsmentioning
confidence: 99%
“…The corresponding probe showed a linear response to l -DOPA in the range of 0–35 μM with an LOD value of 76.18 nM. 37 Therefore, understanding and addressing chiral discrimination based on CQDs is critical for the development and use of safe and effective pharmaceuticals. To the best of our knowledge, this study represents the first and only reported investigation of chiral CQDs that exhibit exceptional performance in the chiral detection of l -DOPA.…”
Section: Introductionmentioning
confidence: 99%